Translational highlights in breast cancer research and treatment: recent developments with clinical impact - Fasching, Peter Andreas; Schneeweiss, Andreas; Kolberg, Hans-Christian; Ettl, Johannes; Fehm, Tanja; Overkamp, Friedrich; Lüftner, Diana (Current opinion in obstetrics and gynecology, 2019)
Purpose of reviewOver the last decades the time which is needed to translate a preclinical finding or idea in the clinic has reduced continuously. Especially but not only for breast cancer the number of tested drugs and targeted pathways have increased immensely. In addition, the introduction of imm